2020
DOI: 10.1001/jamaoto.2020.1496
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of the Progression of Vertical Semicircular Canal Dysfunction and Increased Vestibular Endolymphatic Hydrops in Patients With Early-Stage Ménière Disease

Abstract: IMPORTANCE Vertical semicircular canals and endolymphatic hydrops play important roles in the pathophysiological mechanisms of Ménière disease. However, their characteristics and associations with disease progression during medical treatment have not been determined. OBJECTIVE To examine the function of both the horizontal and vertical semicircular canals in patients with Ménière disease and to evaluate the change in endolymphatic hydrops volume during medical treatment, including treatment with diuretic thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Although the hearing level in the affected ear is reported to correlate with EH volume ( 22 ), the decrease in cochlear EH might not have improved the hearing level in this case. In MD, hearing levels worsen, and EH volume develops over time ( 23 ). The EH-reducing effect of a PPT device might have stopped the hearing deterioration, in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Although the hearing level in the affected ear is reported to correlate with EH volume ( 22 ), the decrease in cochlear EH might not have improved the hearing level in this case. In MD, hearing levels worsen, and EH volume develops over time ( 23 ). The EH-reducing effect of a PPT device might have stopped the hearing deterioration, in our patient.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 However, our subjects did not present vertiginous or cochlear symptoms. Fukushima et al 14 reported a relationship between the progression of vertical semicircular canal dysfunction and increased vestibular endolymphatic hydrops in patients with early stage MD.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of ongoing studies is currently aimed at targeting the correlation between the morphologic findings and the symptomatology ("the whole symptoms triad") and, especially, with the results of the functional audio-vestibular testing and with the outcomes of treatment (37,41,48,51,52,62,63,67). In general, the literature agrees that the presence of EH at MRI, independently from the cut-off values for definition of vEH, strongly correlates with the side of the disease in MD patients (47,50), but it lacks specificity in differentiating MD from other inner ear disturbances, in the absence of clinical/instrumental confirmation (64).…”
Section: Recent Advancesmentioning
confidence: 99%